Voice of Energy, Information, Inspiration in Education (Dina Dzhusubaliyeva). (Journal of Educational Sciences, 2018)
20 Sep 2017 was the anniversary of doctor pedagogical Sciences, Professor, academician International Academy Informatization academician International Academy of science teacher education Dina Lufthavne Dzusubalieva.